Masstige, Brand Love, and Brand Loyalty: Insights from Over-The-Top (OTT) Platforms - Arora, Garima; Madaan, Dr. Vandana; Singh, Dr. Sultan (International Journal of Accounting and Economics Studies, 2025)
Masstige marketing is an approach to promoting prestigious goods and services among numerous ‎consumers. Materialistic people often exhibit deep love for brands that provide high social status. ‎Brand love can have an enormous effect on users, particularly increasing brand loyalty. Online ‎streaming, which was considered a luxury, has become steadily more common among a large ‎number of Indians. For this reason, the current survey sought to ascertain the impact of masstige ‎on viewers’ loyalty to OTT (Over-the-Top) brands, whereby brand love serves as an intervening ‎factor. Data from 247 respondents were collected via an adapted questionnaire, and valid ‎responses were evaluated using statistical analyses. The outcomes of research show that masstige ‎tactics played a major role in creating an intense love for a brand, which is considered significant ‎for achieving substantial rises in brand loyalty. When it comes to influencing brand loyalty, the ‎results of the IPMA (Importance Performance Map Analysis) reveal that brand love is more ‎important than masstige. Besides this, it is also important for the brand to develop a positive ‎emotional connection as well as the passion-driven behaviour of the consumers concerning the ‎OTT (Over-the-Top) brands for influencing brand loyalty. Furthermore, the research also provides ‎the financial and policy implications for the OTT service providers‎.
Keywords: Masstige, Brand Love; Brand Loyalty; OTT (Over-the-Top); IPMA (Importance Performance Map ‎Analysis)‎.